Manufacturing Sustainability Via OEE Measures: A Conceptual Model - Wan Mahmood, Wan Hasrulnizzam; Abdullah, Ilyana; Muhammad Hafidz Fazli , Md Fauadi (Scientific.Net, 2015)
This paper proposes a conceptual model on the achieving of the manufacturing sustainability through an established performance measure so called Overall Equipment Effectiveness (OEE) based on literature study. It examines the measures of overall equipment effectiveness that consist of contributing factors, availability, performance, and quality; and the sustainable manufacturing components including environmental conservation, social efficiency, and economic vitality. The measures of the OEE are required some modification to enhance the accomplishment of the sustainability in manufacturing. Besides, the measures are nevertheless possible to improve productivity through the identification and elimination of manufacturing big loses. It can be used as an initial reference for manufacturers to consider overall equipment effectiveness to advance the goal of manufacturing sustainability.